Dynamic and static interfacial bonding properties of CFRP–concrete subjected to freeze–thaw cycles. (March 2022) - Zhang, Zhen-wen; Zhang, Zi-hua; Wang, Xuan; Zhou, Chun-heng
Abstract: Dynamic and static single-lap shear tests of 144 carbon-fiber-reinforced polymer (CFRP)–concrete specimens subjected to freeze–thaw cycles were completed. Static and dynamic single-lap shear tests of CFRP–concrete specimens subjected freeze–thaw cycles were conducted, and a total of 32 groups of specimens with different strength grades, numbers of freeze–thaw cycles, and loading rates were tested. The corresponding dynamic and static interfacial bonding properties were carefully analyzed based on the failure characteristics, strain distributions on the CFRP surface, interfacial shear stress, interfacial average peak shear stress, interfacial fracture energy, interfacial shear strength, effective bonding length, and interfacial bond-slip curves. This study finds that the resistance to the freeze–thaw cycles of concrete was the most important factor affecting the static and dynamic properties of the CFRP–concrete interface, as well as the deterioration effect of freezing and thawing on the concrete was more severe than the effect of the erosion of the glue layer. Further analysis showed that the dynamic properties of the CFRP–concrete interface decreased as the number of freeze–thaw cycles increased. The freeze–thaw cycle could cause the embrittlement of the interface and decrease its dynamic energy absorbing ability. Finally, the refined finite element method with the concrete-damaged-plasticity (CDP) model was proposed to reveal the damage process of the CFRP–concrete interface.